Registrierende Härtemessung an neutronenbestrahlten Materialien bei hohen Temperaturen - Valentin Brabänder, Alexander (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
The present work investigates neutron-irradiated EUROFER97 by high-temperature indentation. Before, a test procedure is defined for the prototype device Karlsruhe high-temperature indenter. The procedure leads to a quality of the test results at high temperatures comparable to commercial devices at room temperature. The results contribute to a better understanding of structural materials of future fusion reactors.